Bosentan for the treatment of adult pulmonary hypertension. (January 2011) - Dwyer, Nathan; Kilpatrick, David
Pulmonary hypertension is a severe progressive disease with a marked morbidity and a high mortality attributed to right heart failure. Bosentan, a dual endothelin receptor antagonist, is an effective and well-tolerated oral therapy for the management of pulmonary arterial hypertension (PAH; WHO group 1 pulmonary hypertension). Bosentan improves cardiopulmonary hemodynamics, exercise capacity, WHO functional class and quality of life, as well as delaying time to clinical worsening in patients with PAH. This article reviews the role of endothelin-1 in the pathogenesis and progression of PAH, the diagnosis of PAH and the pharmacology of bosentan, and summarizes the current available evidence for the safety and efficacy of bosentan for the treatment of PAH as a monotherapy and combination therapy, as well as its role in the management of other forms of pulmonary hypertension.